Using Writing Tasks as an Assessment in Extensive Reading in a University-Level EFL Course - Pratama Irwin Talenta; Maria Dimitri; Angie Pavita (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Extensive reading (ER) needs to be easy, enjoyable and lots of reading (Nation & Macalister, 2020). When learners read extensively, they read for pleasure and recreation, instead of studying vocabulary, grammar, idioms and looking up texts. This study seeks to assess students' understanding of ER through writing tasks, in other words, ER needs to be task-based. This study was a descriptive qualitative by using observations, questionnaires, and interviews as data collection. The participants in this study were students in the third semester of English education department at Universitas Nasional Karangturi Semarang who attended the extensive reading class. As a result, most students found it easy to use the writing task as an exercise, either while the student was reading the book or after they had finished reading the book. Second, the students were willing to be involved in creating portraits of the characters and writing illustration descriptions, including descriptions of the selected features. The research stages and results are recommended as a reference for teachers, lecturers and researchers in assessing reading literacy.